Rapunzel - Zelinsky, Paul O. (New York : Dutton Children's Books, 1997)
A retelling of a folktale in which a beautiful girl with long golden hair is kept imprisoned in a lonely tower by a sorceress. Includes a note on the origins of the story.
Keywords: Caldecott Medal; Fairy tales; Folklore